Kebijakan Fiskal dalam Islam - Lilik Rahmawati (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2008)
Entering the new millennium, Muslims are concerned with historical expectations as well as formidable challenges especially about economic issues. In term of Islamic economic principles, Islamic economy acknowledges the theologically responsible human freedom, the rights of ownership on the basis of betterment, the prohibition of property stockpiling which in fact are fit with human instinct.Â On the fulfillment of human needs, Islam orders the creation of a state. The role of Islamic state is very important in ensuring prosperity and the needs of its people. in doing so, an Islamic state have policies, including fiscal management.The article concludes that fiscal policy of the ancient regimes of Roman empire, Greece, Egypt and India was in the hand of the government. On the other hand, fiscal policy is an obligation of a stat toward its people. therefore fiscal policy is not a requirement for economic improvement or prosperity enhancement of the people. rather, it is about the creation of fair economic distribution mechanism. The sources of income of an Islamic state is faiâ€™, ghanimah, kharaj, jizyah, ushur and khumus. as to zakat, it is a self-sufficient social assistance which is a moral obligation for the rich to help those who are poor and neglected.